Temozolomide-based radio-chemotherapy for newly diagnosed pediatric high-grade gliomas (HIT-HGG-2007): A prospective, multicenter, single-arm, phase II trial - Michael Karremann; Thomas Perwein; André O. von Bueren; Gerrit H. Gielen; Martin Benesch; Gunther Nussbaumer; Lea L. Friker; Andreas Waha; Dominik Sturm; David T.W. Jones; Olaf Witt; Stefan M. Pfister; et al. (EJC Paediatric Oncology, 2025)
Background: The HIT-HGG-2007 trial investigated temozolomide (TMZ) radio-chemotherapy for pediatric patients with high-grade gliomas (pHGG) to demonstrate therapeutic non-inferiority compared to previous intensive radio-chemotherapy regimens (HIT-GBM-C/-D). Methods: Between June 2009 and December 2016, 456 patients were enrolled into this international, prospective, single-arm, multicenter phase II trial in Germany, Austria, and Switzerland of whom 438 patients were evaluable for confirmatory analysis. Patients from the HIT-GBM-C/-D trials served as historic control (n = 439). Tumors of both cohorts with available tissue were re-classified according to the 2021 WHO classification of CNS tumors (n = 140). Results: Regarding event-free-survival (EFS) rate at 6 months, non-inferiority of the HIT-HGG-2007 regimen was confirmed (p = 0.0125). In terms of exploratory analyses, median EFS and overall survival (OS) was 9.5 months (95 % confidence interval [CI95], 8.9–10.4) and 14.7 months (CI95, 13.5–16.3), superior to intensive chemotherapy regimens (p < 0.0001 and p = 0.0328). EFS and OS remained superior after re-classification of tumors according to WHO2021 criteria. TMZ radio-chemotherapy had lower rates of severe hematological, gastrointestinal, and hepatic toxicity compared to HIT-GBM-C/-D. Younger age, WHO grade IV histology, tumor location in the brainstem or basal ganglia, and lower extent of resection were independent adverse risk factors for OS and EFS. MGMT gene promoter methylation status had no impact on EFS and OS. Conclusions: The HIT-HGG-2007 trial demonstrated non-inferiority compared with intensive chemotherapy regimens. MGMT promotor methylation status had no impact on survival. Exploratory analysis supports treatment of newly diagnosed non-pontine pHGG according to the HIT-HGG-2007 regimen due to improved EFS and OS rates together with a favorable toxicity profile.